"Instant gene bank" method adapted for cloning mutant benomyl-resistance allele in replicative vector in Aspergillus nidulans - A. Y. Aleksenko (Fungal Genetics Reports, 1994)
The "instant gene bank" method for gene cloning by mutant complementation in Aspergillus nidulans uses ligation in vivo of donor DNA and an autonomously replicating plasmid to obviate the necessity for an intermediate bacterial host (Gems et al. 1994 Mol. Gen. Genet. 242:467-471). Its applicability was demonstrated by cloning the TrpC gene from Penicillium canescens. Here we report a modification of the method for cloning a mutant allele promoting benomyl resistance from Penicillium canescens, with the final aim of using it as a transformation selectable marker.